A short review of nanographenes: structures, properties and applications. (18th April 2018) - Dai, Yafei; Liu, Yi; Ding, Kai; Yang, Jinlong
ABSTRACT: Graphene has attracted great interest in the science and technology since it was exfoliated mechanically from the graphite in 2004. Although graphene has various potential applications, its practical applications are constrained enormously by its serious drawbacks, such as zero band gap, tendency of aggregation between layers and hydrophobicity, which mainly caused by the infinite planar hexagonal structure of graphene. Considering that the structural defects in the honeycomb lattice and the edges of graphene break the infinite structure and thus change the properties, which may improve the application efficiency, nanographene (NG) is proposed and attracts extensive attention. In this work, we review the structures of multifarious well-defined NGs synthesised in recent experiments. The effects of the shape, size, edges and substituents of NGs to the properties are discussed in detail and the regulation for various properties of NG is analysed. For the well-defined NGs, including planar and non-planar ones, the challenges and perspectives of their potential applications in nonlinear optical material, gas molecular detector and gas separation material, hydrogen storage material, and hole-transporting material in perovskite solar cells are envisioned. Abstract :